Transforming Anti Corruption Education to Strengthen Integrity Values among University Students in the Digital Era: A Literature Review - Mohammad Hafil; Ramadhan Arifin Mansyur; Aditya Abdi Pratama; Yeni Tri Nur Rahmawati (Pusdikra-Publishing.com, 2025)
Anti-corruption education has become a strategic instrument in strengthening integrity values among university students, particularly in the digital era characterized by rapid information flows, data transparency, and technology-based social interactions. However, existing studies indicate that the implementation of anti-corruption education in higher education institutions still faces several challenges, including the dominance of cognitive-oriented approaches, limited pedagogical innovation, and inconsistencies between taught values and social realities experienced by students. This article aims to comprehensively examine the transformation of anti-corruption education in strengthening students’ integrity values in the digital era through a literature review approach. The scope of this study focuses on anti-corruption learning strategies, the utilization of digital media, the integration of local cultural values, and the influence of social environments on integrity internalization. The method employed is a literature review by identifying, reviewing, and critically analyzing selected articles from relevant national and international journals published within the last ten years. The findings indicate that effective transformation of anti-corruption education requires an integrated approach that combines digital technology utilization, character education, and contextually grounded socio-cultural values. Anti-corruption education should not merely function as knowledge transmission but as a continuous process of shaping ethical attitudes and behaviors. Therefore, strengthening literature-based anti-corruption education is expected to foster students’ critical awareness, moral commitment, and strong integrity in addressing global challenges in the digital era.